Making the case for multilingual scholarly communication / Plaidoyer pour une communication savante multilingue - Bowker, Lynne; Laakso, Mikael; Pölönen, Janne (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
A scholarly communication ecosystem with one dominant language presents numerous inequities. Implementing multilingualism is complex and there is no single strategy to achieve it. Rather, multilingualism can take different forms, and small steps taken by different actors can add up to increase linguistic diversity. This commentary unpacks some of the complexities involved in multilingual scholarly communication and offers some concrete recommendations for moving forward.